KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM PENYELENGGERAAN PROGRAM UNGGULAN SEKOLAH DIGITAL - Syamsuddin; Dwi Nugroho Hidayanto; Mulawarman, Widyatmike Gede; Masruhim, Amir; Haryaka, Usfandi; Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the weak implementation of the Digital School Program at SMA Negeri 6 Samarinda, which was launched in 2023 as a response to the demands for educational transformation in the digital era. The study aims to describe the principal's managerial competencies in planning, organizing human resources, actuating, monitoring, and identifying obstacles in the program. This study used qualitative approaches, with data sources obtained through in-depth interviews with various stakeholders, field observations, and documentation studies. The analysis technique was based on Miles and Huberman's guidelines, which consist of condensation, data display, and conclusion drawing. The results showed that the failure of implementation was mainly due to the weakness of the principal's managerial competencies, especially technical and interpersonal competencies. In planning, the program lacked measurable long-term goals and had very limited stakeholder participation. The organization of the team suffered from a lack of clarity in its structure, division of tasks, and coordination mechanisms, which relied solely on WhatsApp without sufficient involvement from the principal. The actuating of the program was not supported by clear and detailed work guidelines or a motivation system that met the expectations of the Digital School Team, resulting in a drastic decline in the team's commitment. Monitoring was not carried out systematically without clear performance standards, structured monitoring mechanisms, or periodic evaluations. The main obstacles included effective leadership, uneven digital competence among teachers, and limitations in infrastructure and funding. The main reason for this is weak managerial and leadership skills. The study shows that the success of tech-based innovation programs isn't just about having a brilliant vision, but also depends a lot on the principal's technical and interpersonal skills in managing change.